Increased Detection of Colorectal Polyps in Screening Colonoscopy Using High Definition i-SCAN Compared with Standard White Light - Kim, Woo Jung (Clin Endosc, 2016)
BACKGROUND/AIMS: The aim of this study was to evaluate the efficacy of high definition (HD) i-SCAN for colorectal polyp detection in screening colonoscopy. METHODS: We retrospectively analyzed the records of 501 patients who had undergone screening colonoscopy performed by three endoscopists with either HD i-SCAN (n=149) or standard white light (n=352) from January 2, 2014 through June 30, 2014. Patient information and inter-endoscopist variation as well as polyp number, endoscopic findings, and pathologic characteristics were reviewed. RESULTS: The detection rates of colorectal and neoplastic polyps were significantly higher using HD i-SCAN than standard white light colonoscopy (52% vs. 38.1%, p=0.004 for colorectal polyps; and 37.2% vs. 27.9%, p=0.041 for neoplastic polyps). Analysis of endoscopic findings revealed no difference in detected polyp size between HD i-SCAN and standard white light colonoscopy (4.59±2.35 mm vs. 4.82±2.81 mm, p=0.739), but non-protruding polyps were more commonly detected by i-SCAN than by standard white light colonoscopy (24.6% vs. 13.5%, p=0.007). CONCLUSIONS: Colonoscopy using HD i-SCAN had a significantly higher detection rate of colorectal polyps, including neoplastic polyps, because of improved sensitivity for detecting non-protruding lesions.